WARCreate - Rivando, Ryan (Emerging Library & Information Perspectives, 2024)
WARCreate is an open-source Google Chrome add-on that allows users to archive web pages as .WARC files with a single click, created by Mat Kelly and Michele Weigle at Old Dominion University. This tool addresses the limitations of other web archiving services like the Wayback Machine by enabling users to independently archive specific web pages, including those behind passwords or with unique geolocations. Its applications in Library and Information Science (LIS) include preserving digital content for research and teaching, and supporting the ethical archiving of sensitive information. Despite some initial usability challenges and a need for more comprehensive support materials, WARCreate remains a valuable tool for capturing and preserving web data.